USE OF ULTRA COARSE DROPLETS AT DIFFERENT SPRAY VOLUMES TO CONTROL WEEDS WITH DICAMBA AND GLYPHOSATE HERBICIDES - Cunha, João P. A. R. da; Antuniassi, Ulisses R. [UNESP]; Chechetto, Rodolfo G.; Palhano, Matheus G.; Ovejero, Ramiro F. L.; Deon, Aline (FapUNIFESP (SciELO), 2022)
The use of ultra-coarse droplets for herbicide application reduces the risk of drift but may compromise the coverage and efficacy of the treatment. The objective of this work was to evaluate the use of ultra-coarse droplets, in different spray volumes, in the application of dicamba herbicide in association with glyphosate, for the control of weeds in two field trials. The first trial was conducted in a 5 x 2 factorial design, with five spray volumes (58, 72, 96, 144, and 177 L ha-1) and two air induction flat-fan spray tips (MUG 110015 - MagnoJet and TTI 110015 - Teejet). The control efficiency of Commelina benghalensis and the spray deposition on the target were evaluated by detecting a tracer using spectrophotometry. The second was conducted in a 2 x 2 factorial scheme, using two volumes (100 and 125 L ha-1) and two tips (MUG 11002 and TTI 11002). The control efficiency of Conyza spp. and fresh matter were evaluated. The different spray volumes and tips did not differ in relation to the deposition of the tracer. The use of ultra-coarse droplets was adequate for weed control. The TTI and MUG tips gave similar and adequate control performance starting at 96 L ha-1. Increasing the volume above 100 L ha-1 did not result in better control.
Keywords: Application technology; Chemical control; Droplet spectrum; Spray nozzles